PENDAMPINGAN DAN PENGEMBANGAN KELOMPOK BERMAIN MEKAR KELURAHAN SIDOWAYAH KECAMATAN REMBANG KABUPATEN REMBANG - Anik Nurhidayati; Muhammad Tahwin; Muhammad Asrori (Buletin Abdi Masyarakat, 2023)
The Community Service Program that will be carried out is Assistance in Management and Development of the Mekar Play Group, Sidowayah Village, Rembang District. Identification of problems faced, management management is still very simple, marketing strategy is still limited, general administration management and financial administration are still limited. The concept of activities in this community service program is training and mentoring. The training provided includes: management management, marketing strategy, general administration and financial administration that have been implemented. The results of the mentoring and training include being registered at the Central Java sipendi, promotion through social media and media widely. The Mekar Play Group, Sidowayah Village, Rembang District, has been verified in the Central Java sipendi system for both teachers and students. Have online marketing media including Instagram, Facebook and brochures. Publication on several social media. Keywords: training, sipendi, marketing strategy